2022
DOI: 10.3389/fphar.2022.907713
|View full text |Cite
|
Sign up to set email alerts
|

α7 Nicotinic Acetylcholine Receptor May Be a Pharmacological Target for Perioperative Neurocognitive Disorders

Abstract: Background: The α7 nicotinic acetylcholine receptor (α7nAChR) is a promising therapeutic target in neurodegenerative diseases. This study examined the effects of surgery and anesthesia on α7nAChR expression in the central nervous system and determined the mechanisms by which α7nAChR mediates neuroprotection in perioperative neurocognitive disorders (PNDs) in aged mice.Methods: Eighteen-month-old male C57BL/6J mice underwent aseptic laparotomy under isoflurane anesthesia, maintaining spontaneous ventilation to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…Mice with cognitive impairment due to intracerebroventricular streptozotocin injection were not only improved in memory tests by alpha7 nAChR agonist GTS-21 but the drug also blocked the streptozotocin-induced overproduction of TNFalpha, IL-1beta, and IL-6 in the hippocampus and the cortex [ 51 ]. Alpha7 nAChR agonists also decrease IL-1beta levels and increase BDNF levels in mice with perioperative neurocognitive disorder [ 52 ]. Positive allosteric modulators (PAM) of the alpha7 nAChR also effectively reduce neuroinflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Mice with cognitive impairment due to intracerebroventricular streptozotocin injection were not only improved in memory tests by alpha7 nAChR agonist GTS-21 but the drug also blocked the streptozotocin-induced overproduction of TNFalpha, IL-1beta, and IL-6 in the hippocampus and the cortex [ 51 ]. Alpha7 nAChR agonists also decrease IL-1beta levels and increase BDNF levels in mice with perioperative neurocognitive disorder [ 52 ]. Positive allosteric modulators (PAM) of the alpha7 nAChR also effectively reduce neuroinflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that neuroinflammation was postulated as a pathological mechanism in AD (Kinney et al, 2018), several studies attempt to point out that α7 nAChRs may be a key element in AD pathophysiology (Hoskin et al, 2019). Moreover, α7 nAChRs influence the expression of glutamate receptors and neurotrophic factors, making them a key element for targeting cognitive decline in AD (Cai et al, 2022; Medeiros et al, 2014; Roberts et al, 2021; Wei et al, 2022).…”
Section: α7 Nachr As a Pharmacotherapy Tool In Memory Deficits And Co...mentioning
confidence: 99%
“…Moreover, Ras GTPase inhibitor enhanced hippocampal brain‐derived neurotrophic factor (BDNF) concentration, which was reversed by the antagonism of α7 nAChRs (Cai et al, 2022). In line with this research, a mice model of perioperative cognitive disorder was used for assessing the effects of α7 nAChR modulation on a hippocampal‐dependent spatial learning task (Wei et al, 2022). Following an aseptic laparotomy, these authors found a decrease of BDNF protein expression in the hippocampus, which was reversed by α7 nAChR activation and promoted by their inhibition.…”
Section: α7 Nachr As a Pharmacotherapy Tool In Memory Deficits And Co...mentioning
confidence: 99%
“…In second experiment, K252a (an antagonist of the TrkB receptor, MCE, 99533-80-9) diluted in 0.1% methyl sulfoxide (DMSO) was intraperitoneally administered at 25 μg/kg per injection daily for 15 days before hUC-MSC transplantation. Based on previous reports, a low concentration of K252a was selected to avoid any unwanted effects [25][26][27]. The same amount of DMSO and normal saline were administered intraperitoneally to mice in other groups.…”
Section: Pnd Animal Model and Drug Administration/huc-msc Transplanta...mentioning
confidence: 99%
“…An escape platform (diameter, 100 mm) was placed in the first quadrant and submerged 15 mm below the water surface. The MWM test consists of 5 days of spatial acquisition trials, and a 1-day probe trial was performed as previously described [26,28]. In the spatial acquisition trials, mice were trained to find the hidden platform within 60 s using distinctive distal visual cues around the apparatus over four consecutive trials conducted once per day.…”
Section: Mwm Testmentioning
confidence: 99%